Cryobiopsy in the diagnosis of idiopathic pulmonary hemosiderosis: a case report - Kania, Aleksander; Misiaszek, Magdalena; Vašáková, Martina; Szlubowski, Artur; Bugalho, Antonio; Pankowski, Juliusz; Szołkowska, Małgorzata; Roden, Anja C.; Celejewska-Wójcik, Natalia; Nastałek, Paweł; Gnass, Maciej; Sładek, Krzysztof (Journal of Thoracic Disease, 2019)
Transbronchial lung cryobiopsy (TLCB) was first described in 2009 (1) and since then it has become a common diagnostic method in interventional pulmonology. Being a safe and cost-effective method, it has been used to diagnose interstitial lung diseases (ILDs) (2,3). It is estimated that its diagnostic yield varies from 75% to 91% (4-6) and it is superior to traditional transbronchial lung biopsy (TBLB) (6,7) in terms of effectiveness. Although not yet as effective as open lung biopsy, its efficacy and safety are unquestionable (8,9). Consequently, it becomes a good alternative to open lung biopsy (10) and is always the first recommended procedure (11). While several interstitial diseases have been diagnosed by histopathological analysis of cryobiopsy samples, there are no studies, which would refer to idiopathic pulmonary hemosiderosis (IPH) confirmed by this diagnostic method. Here, we present what we believe to be the first IPH case to be confirmed by TLCB.